Disparity in Lung Cancer Screening Among Smokers and Nonsmokers in China: Prospective Cohort Study - Le Wang; Youqing Wang; Fei Wang; Yumeng Gao; Zhimei Fang; Weiwei Gong; Huizhang Li; Chen Zhu; Yaoyao Chen; Lei Shi; Lingbin Du; Ni Li (JMIR Publications, 2023)
BackgroundLow-dose computed tomography (LDCT) screening is effective in reducing lung cancer mortality in smokers; however, the evidence in nonsmokers is scarce. ObjectiveThis study aimed to evaluate the participant rate and effectiveness of one-off LDCT screening for lung cancer among smokers and nonsmokers. MethodsA population-based prospective cohort study was performed to enroll participants aged between 40 and 74 years from 2013 to 2019 from 4 cities in Zhejiang Province, China. Participants who were evaluated as having a high risk of lung cancer from an established risk score model were recommended to undergo LDCT screening. Follow-up outcomes were retrieved on June 30, 2020. The uptake rate of LDCT screening for evaluated high-risk participants and the detection rate of early-stage lung cancer (stage 0-I) were calculated. The lung cancer incidence, lung cancer mortality, and all-cause mortality were compared between the screened and nonscreened groups. ResultsAt baseline, 62.56% (18,818/30,079) of smokers and 6% (5483/91,455) of nonsmokers were identified as high risk (P<.001), of whom 41.9% (7885/18,818) and 66.31% (3636/5483) underwent LDCT screening (P<.001), respectively. After a median follow-up of 5.1 years, 1100 lung cancer cases and 456 all-cause death cases (116 lung cancer death cases) were traced. The proportion of early-stage lung cancer among smokers was 60.3% (173/287), which was lower than the proportion of 80.3% (476/593) among nonsmokers (P<.001). Among smokers, a higher proportion was found in the screened group (72/106, 67.9%) than the nonscreened group (56/114, 49.1%; P=.005), whereas no significance was found (42/44, 96% vs 10/12, 83%; P=.20) among nonsmokers. Compared with participants who were not screened, LDCT screening in smokers significantly increased lung cancer incidence (hazard ratio [HR] 1.39, 95% CI 1.09-1.76; P=.007) but reduced lung cancer mortality (HR 0.52, 95% CI 0.28-0.96; P=.04) and all-cause mortality (HR 0.47, 95% CI 0.32-0.69; P<.001). Among nonsmokers, no significant results were found for lung cancer incidence (P=.06), all-cause mortality (P=.89), and lung cancer mortality (P=.17). ConclusionsLDCT screening effectively reduces lung cancer and all-cause mortality among high-risk smokers. Further efforts to define high-risk populations and explore adequate lung cancer screening modalities for nonsmokers are needed.